Social protection versus economic flexibility : is there a trade-off? - Blank, Rebecca M. (NBER Comparative labor markets series., 1994)
As the Clinton administration considers major overhauls in health insurance, welfare, and labor market regulation, it is important for economists and policymakers to understand the impact of social and welfare programs on employment rates. This volume explores how programs such as social security, income transfers, and child care in Western Europe, the United States, and Japan have affected labor market flexibility-the ability of workers to adjust to fast-growing segments of the economy. Does tying health insurance to employment limit job mobility? Do housing policies inhibit worke.